Morphological Interpretation in Al-Qamus Al-Muhit (Journal of the College of Basic Education, 2024)
This research aims to study one of the methods of lexicographic interpretation, namely the morphological interpretation method, in one of the prominent Arabic dictionaries, which is Al-Qamus Al-Muhit. This is due to its importance in revealing lexicographic meanings and morphological indications of linguistic materials. Al-Qamus Al-Muhit included many examples of morphological interpretation based on two important elements: the morphological element that indicates the morphological meaning and the derivational element that indicates the derivational meaning. The author of Al-Qamus Al-Muhit chose several morphological terms to express the morphological meaning, sometimes unified, and other times using two or more terms to express a single morphological meaning. Sometimes the terms were not unified, and compound phrases were also used to express that meaning in several instances. As for the derivational element, it sometimes stemmed from the root of the word to be interpreted and sometimes from another root. Al-Qamus Al-Muhit is one of the Arabic dictionaries that relied on direct and indirect sources in its morphological interpretation, whether morphological or lexicographic. The author of the dictionary mentioned a portion of those sources in its introduction, and the presence of identical examples between dictionaries or sources from those dictionaries and sources, and Al-Qamus Al-Muhit, clearly indicates Al-Firuzabadi's reliance on these sources in his interpretations, especially the morphological ones.